Performance and kinetics of algal-bacterial photobioreactor (AB-PBR) treating septic tank effluent - Chawalit Chaiwong (2019)
© IWA Publishing 2018. Septic tank effluent contains high organic and nutrient contents. This study aimed to evaluate treatment performance of an algal-bacterial photobioreactor (AB-PBR) treating the septic tank effluent. The experimental unit employed a transparent plastic medium made from recycled drinking water bottles for attached-growth biofilm. Red LED lamp (light intensity 100 μmol/m 2 /s) was applied as an energy source for the growth of algal-bacterial biofilm in the AB-PBR. The experimental results showed that AB-PBR operated at the hydraulic retention time (HRT) of 3 days gave the highest chemical oxygen demand (COD), total nitrogen (TN) and total phosphorus (TP) removal efficiencies of 64, 45 and 35%, respectively, by which the effluent COD concentrations could meet the effluent standards of Thailand, but the effluent TN and TP concentrations needed to be further removed. The Stover-Kincannon model was applied to determine the kinetic values of COD and TN removals with R 2 values greater than 0.8. Microbiological examinations indicated Chlorella sp. is the predominant algal species growing in the AB-PBR, while the amplicon sequencing information analytical results revealed the bacterial phylum of Proteobacteria to be the predominant bacterial group.